2022
DOI: 10.5005/jp-journals-10071-24045
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Changes in COVID-19 Patients: A Hospital-based Descriptive Study

Abstract: A bstract Background Coronavirus disease-2019 (COVID-19) infection is a multisystem disease not restricted to the lungs. It has a negative impact on the cardiovascular system by causing myocardial damage, vascular inflammation, plaque instability, and myocardial infarction. The presence of myocardial injury is a poor prognostic sign. Electrocardiogram (ECG), a simple bedside diagnostic test with high prognostic value, can be employed to assess early cardiovascular involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The higher prevalence of hypertension and diabetes mellitus among patients again highlights the fact that these are major risk factors toward infection with SARS-CoV-2. A study that is done in India by Kaliyaperumal et al,21 consisted of 315 cases with 81% of patients having cardiac involvement among which 36.8% patients had diabetes mellitus and 30.5% had history of hypertension. In this study, systemic hypertension had significant correlation with ischemic changes in ECG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher prevalence of hypertension and diabetes mellitus among patients again highlights the fact that these are major risk factors toward infection with SARS-CoV-2. A study that is done in India by Kaliyaperumal et al,21 consisted of 315 cases with 81% of patients having cardiac involvement among which 36.8% patients had diabetes mellitus and 30.5% had history of hypertension. In this study, systemic hypertension had significant correlation with ischemic changes in ECG.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, as per the studies there is not only myocardial injury but conduction system involvement is also common as well in patients with infection with SARS-CoV-2. A study is done in India by Kaliyaperumal et al,21 including 315 patients where the abnormal ECG findings included ST elevation in 8.6% patients, ST depression in 3.2% patients, T wave inversion in 23.8% patients, sinus bradycardia in 12.7% patients, prolonged PR interval in 2.9% patients, and irregular rhythm in 2.9% patients. There was higher prevalence of cardiovascular abnormality among the severe and moderate category patients as compared to mild category patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors that can cause arrhythmias are myocardial infarction, myocarditis, shock, hypoxia, and electrolyte disturbances. [14] About 27.8% of COVID-19 patients in Wuhan have high troponin levels, which indicates damage to the heart muscle. [15] Damage to the heart muscle of a COVID-19 patient can occur due to a cytokine storm which will make white blood cells stick to blood vessels, thus increasing the risk of thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prolongation in the QRS interval could be the marker of respiratory failure . The European Society of Cardiology recommends routine ECG upon initial assessment and even to monitor treatment progress. , Studies have shown that continuous ECG monitoring during home management of COVID-19 reduces the risk of major adverse events. , Moreover, tracking the oxygen saturation level along with ECG reduces the risk of hospitalization while QRS interval prolongation could be a marker for respiratory failure. This can allow the detection of low levels of oxygen saturation, which is an important parameter indicating severity and progression .…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 Studies have shown that continuous ECG monitoring during home management of COVID-19 reduces the risk of major adverse events. 11 , 12 Moreover, tracking the oxygen saturation level along with ECG reduces the risk of hospitalization while QRS interval prolongation could be a marker for respiratory failure. This can allow the detection of low levels of oxygen saturation, which is an important parameter indicating severity and progression.…”
Section: Introductionmentioning
confidence: 99%